Respostas
respondido por:
0
y= ax+b
3= (-3)*(-2)+b
3=6+b
b = -3
a equação da reta fica:
y = -3x -3
3= (-3)*(-2)+b
3=6+b
b = -3
a equação da reta fica:
y = -3x -3
respondido por:
0
Boa tarde CarlosAdolf
a equação de uma reta com um ponto e o coeficiente angular é
y - Py = m * (x - Px)
Py = 3, Px = -2
y - 3 = -3 * (x + 2)
y - 3 = -3x - 6
y = -3x - 3
a equação de uma reta com um ponto e o coeficiente angular é
y - Py = m * (x - Px)
Py = 3, Px = -2
y - 3 = -3 * (x + 2)
y - 3 = -3x - 6
y = -3x - 3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás